The The Effect of the Discovery Learning Model with Student Worksheets on Students’ Mathematical Concept Comprehension Ability Comprehension Ability - Siti Rahma; Murtafiah; Nursyam Anaguna (Department of Mathematics, Universitas Negeri Padang (UNP), 2025)
Mathematical concept comprehension is essential in learning mathematics. However, students’ comprehension of mathematical concepts is still low. This research aims to determine the effect of the discovery learning model with student worksheets on students’ mathematical concept comprehension ability. The method used in this research is quantitative. The type of research is a quasi-experimental design. Two classes were selected as the research sample using the simple random sampling technique. The instruments used in this research are a test of mathematical concept comprehension abilities and observation sheets of learning implementation. The data analysis techniques used in this research were descriptive analysis and inferential analysis (Independent Sample T-Test). Based on the data analysis results, the research shows that the discovery learning model with student worksheets positively affects students’ mathematical concept comprehension ability. This research implies that discovery learning with students' worksheets can be an effective alternative to improve students’ comprehension of mathematical concepts in classroom practice.